Development of Financial Management and Production Process for Bag Craft SME Workers in Serang Regency - Andreas Tri Panudju; Rina Nopianti; Mochamad Fahru Komarudin; Leni Triana; Prastika Tjeng Suwandi (Jurnal Pengabdian Masyarakat Formosa, 2023)
The development of SMEs through a business empowerment approach needs to pay attention to social and cultural aspects in each region. Based on the analysis of the needs of each UKM and the agreement between the service team and the partner UKMs, the target to be achieved in implementing the service program in the context of solving partner problems is how to improve bookkeeping including aspects of inventory lists, initial balance sheets, diaries, purchase books, books sales, book inventory, calculate profit and loss, make a final balance sheet and be able to calculate the cost of production per unit based on orders or other products, add product types and diversify product designs, and procure machinery ergonomic sewing for SME partners.